(untitled) (Texas Journal of Philology, Culture and History, 2023)
Problems of the categorical organization of crossword puzzles, we have established the specifics of this genre, which is manifested in its discursive integrity - bringing the author’s intention in line with the performance of tasks by the addressee; in hypertext, megatext and graphic connectivity; in the wide information content generated by the consciousness of the author of the crossword puzzle, fixed in tasks and appealing to the consciousness of the addressee, his competence and interpreter; in a special anthropocentricity, realized at the turn of two consciousnesses by an irrelevant addresser, a program of addressing a hypothetical addressee and a real addressee.